2006
DOI: 10.1002/dneu.20324
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and dominance‐associated differences in mushroom body structure in the paper wasp Mischocyttarus mastigophorus

Abstract: Primitively eusocial paper wasps exhibit considerable plasticity in their division of labor. Dominance interactions among nest mates play a strong role in determining the task performance patterns of adult females. We asked whether dominance status and task performance differences were associated with the development of subregions of the mushroom bodies (MB) of female Mischocyttarus mastigophorus queens and workers. We found that the MB calycal neuropils were better developed (relative to the Kenyon cell body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…The gross developmental pattern of M. genalis MB is strikingly similar to both small-and large-colony obligately eusocial bees, wasps and ants in displaying large decreases in Kenyon cell body volume early in adult life and modest increases in neuropil volume with age and experience (Fahrbach 2006;O'Donnell et al 2006). In fact, regardless of any functional interpretation, the N : K ratios of newly emerged and mature (both solitary and social) M. genalis are nearly identical to those of honeybees, despite the massive differences in colony size, social organization and phyletic distance between the two species ( §3 and Withers et al 1993).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The gross developmental pattern of M. genalis MB is strikingly similar to both small-and large-colony obligately eusocial bees, wasps and ants in displaying large decreases in Kenyon cell body volume early in adult life and modest increases in neuropil volume with age and experience (Fahrbach 2006;O'Donnell et al 2006). In fact, regardless of any functional interpretation, the N : K ratios of newly emerged and mature (both solitary and social) M. genalis are nearly identical to those of honeybees, despite the massive differences in colony size, social organization and phyletic distance between the two species ( §3 and Withers et al 1993).…”
Section: Discussionmentioning
confidence: 92%
“…Arneson & Wcislo 2003;Bhadra & Gadagkar 2008). Recent studies have shown a social component to MB plasticity in two species of obligately social paper wasps (Vespidae) with small colonies, which are the only two species studied to date in which dominance is maintained by individual aggressive interactions rather than by pheromones (O'Donnell et al 2006;Molina & O'Donnell 2007Molina et al 2009). Ehmer et al (2001), in contrast, did not find a difference in MB volume between dominant and subordinate wasps of Polistes dominulus wasps, but they did not measure MB subregions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These behavioral differences result from changes in the nervous system induced by social experience. Social status affects neurogenesis in rodents (Kozorovitskiy and Gould, 2004) and crayfish (Song et al, 2007), neuronal size in fish (White et al, 2002), brain morphology in wasps (O'Donnell et al, 2007) and naked mole rats (Holmes et al, 2007), and cell receptor populations in crayfish (Spitzer et al, 2005) and fish (Burmeister et al, 2007). Social status also affects the serotonergic neuromodulation of synaptic responses in both crayfish (Yeh et al, 1996(Yeh et al, , 1997 and fish (Whitaker et al, 2011), and the excitability of neural circuits that produce different behaviors (Krasne et al, 1997;Herberholz et al, 2001;Neumeister et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Fig. 1) Like other eusocial Hymenoptera, paper wasps show behavior-related individual variation in adult brain structure (23)(24)(25). Paper wasp species also differ in the relative amounts of tissue invested in brain regions that process input from different sensory modalities (26).…”
mentioning
confidence: 99%